India in English literature : reading Kim (1901), A Passage to India (1924) and Midnight’s Children (1981) - Kanak, Azimur Rashid (BRAC University, 2015)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Master of Arts in English, 2014.